MicroRNA-490-5p is a novel tumor suppressor targeting c-FOS in human bladder cancer - Lan, Gongbin (Arch Med Sci, 2015)
INTRODUCTION: Recent studies have demonstrated the critical roles of micro-RNAs in tumorigenesis and tumor progression. Here, we describe the regulation and function of miR-490-5p in bladder cancer. MATERIAL AND METHODS: Paired tissue samples were collected from bladder cancer patients (n = 20). Real-time PCR revealed that miR-490-5p expression was significantly down-regulated in human bladder cancer tissues and cells. Also there was an inverse relationship between the expression level of miR-490-5p and the pathological grade of bladder cancer. Western blotting was performed to detect the expression levels of c-FOS and TET1 in 6 matched tumor tissue samples and 4 bladder cell lines. Furthermore, to better understand the underlying mechanisms of miR-490-5p, we conducted gain and loss of function analysis by transfecting bladder cancer T24 cells with chemically synthesized miR-490-5p mimics and inhibitor, respectively. RESULTS: We found that overexpression of miR-490-5p in T24 cells could inhibit cell proliferation and invasion and induce cell apoptosis. Conversely, suppression of miR-490-5p expression induced cell proliferation and invasion, while it inhibited cell apoptosis. In addition, our bioinformatics prediction and experimental data showed that c-FOS was a potential target of miR-490-5p. The expression level of c-FOS was significantly decreased after miR-490-5p overexpression and significantly increased after miR-490-5p suppression, indicating that c-FOS was a target of miR-490-5p. CONCLUSIONS: These findings suggest that miR-490-5p is a novel tumor suppressor, contributing to the carcinogenesis of bladder cancer by targeting c-FOS.